Medical services at the FIFA World Cup Qatar 2022 - Schumacher, Y. O.; Kings, D.; Whiteley, R.; Dharman, A.; Taqtaq, G.; Mc Court, P.; Alkhelaifi, K.; Targett, S.; Holtzhausen, L.; Pieles, G. E.; Dzendrowskyj, P.; Zikria, B. A.; et al. (British Journal of Sports Medicine, 2024)
Objective The Football World Cup is among the biggest sporting events in the world, but data to inform the requirements of medical care for such tournaments are limited. This study describes the athlete and team medical services at the FIFA World Cup Qatar 2022 .